Pengaruh Pengalaman Pelanggan, Kesadaran Merek dan Kepuasaan Pelanggan Terhadap Loyalitas Pelanggan pada Ella Skin Care di Cabang Gentan - Leedi Setiawati; Ari Susanti (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
The purpose of this study was to determine and analyze customer experience, brand awareness and customer satisfaction with ella skin care loyalty at the gentan branch. The population in this study is customer ella skin care. The sample in this study was 100 people with data collection techniques using questionnaires. Hypothesis testing using multiple linear regression analysis then the data is processed with SPSS 20 program. The results of this study indicate that customer experience does not have a significant effect on loyalty. Brand awareness and customer satisfaction have a significant effect on customer loyalty. Keywords: Customer Experience, Brand Awareness, Customer Satisfaction, Customer Loyalty